Peace education as a base for introducing multicultural society to students - Giantomi Muhammad; Nadri Taja; Diden Rosenda; Muhamad Imam Pamungkas (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
In the midst of an unstable world condition with many wars, this is a concern in itself. It seems that education is needed that is in line with efforts to instill the values of peace in preventing social conflict and even war which can harm living creatures. Peace education is considered very appropriate and appropriate to continue to be taught in the current situation and conditions. With that as a basis for introducing a multicultural society that must be upheld by humanity. The aim of this research is to determine the application of peace education as a basis for introducing students to a multicultural society. The research approach was carried out qualitatively accompanied by a case study method. Data collection techniques were carried out using interviews, observation and documentation. With data analysis techniques in the form of data reduction, data interpretation, data triangulation, and conclusions. The results obtained in this research are that peace education is implemented through curriculum integration, knowledge construction, prejudice reduction, equity pedagogy, and empowering school culture. Prioritize an attitude of appreciation, respect and tolerance between teachers and students.Keywords: multicultural society, peace education, war